A Highly Stretchy, Transparent Elastomer with the Capability to Automatically Self‐Heal Underwater. Issue 49 (9th October 2018) - Cao, Yue; Wu, Haiping; Allec, Sarah I.; Wong, Bryan M.; Nguyen, Dai‐Scott; Wang, Chao
Abstract: Polymer materials that are able to self‐heal in humid conditions or even in water are highly desirable for their industrial applications. However, the development of underwater self‐healing polymer materials is very challenging since water molecules can readily disturb traditional noncovalent bonds, such as saturate the hydrogen bonds, coordinate with the metal cation, as well as solvate the ions. Here, a new type of dipole–dipole interactions is employed as the driving force, combining with highly polar and hydrophobic fluorinated polymers, to successfully demonstrate an underwater self‐healing elastomer. The polymer materials are transparent and stretchable. They can remain stable underwater for months without significant decay of mechanical properties. Upon mechanical damage, the material is able to self‐heal automatically in air, underwater, and under very harsh aqueous conditions (including seawater, highly acidic media, and highly basic media, etc.). Abstract : Underwater self‐healable materials are in high demand. Most of them are sensitive to their environment, such as the pH conditions. An elastomer with high transparency, high stretchability, and autonomous self‐healing capability based on dipole–dipole interactions is reported. The material is healable in air, underwater, and other harsh aqueous conditions.